Unsteady heat transfer during encapsulation оf dispersed materials in quasi-liquefied state - Nagursky, O.; Gumnitsky, Ya.; Vaschuk, V. (Publishing House of Lviv Polytechnic National University, 2015)
Experimental and analytical investigations of the heat transfer process during encapsulation of dispersed materials in quasi-liquefied state are presented. The heattransfer coefficients for different types of materials have been determined during their heating depending on air rate. Наведено експериментально-аналітичні дослідження процесу теплообміну під час капсулювання дисперсних матеріалів у стані псевдозрідження. Визначено коефіцієнти тепловіддачі під час нагрівання дисперсного матеріалу у стані псевдозрідження у залежності від швидкості повітря для різних типів матеріалів.
Нестаціонарний теплообмін під час капсулювання дисперсних матеріалів у стані псевдозрідження
Keywords: нестаціонарний теплообмін; кінетика; псевдозрідження; дисперсний матеріал; unsteady heat transfer; kinetics; quasiliquefaction; dispersed material